Laboratory and field evaluation of the STANDARD Q and Panbio™ SARS-CoV-2 antigen rapid test in Namibia using nasopharyngeal samples - Iyaloo Konstantinus; Douglas Chiwara; Emmy-Else Ndevaetela; Victoria Ndarukwa-Phiri; Nathalia! Garus-oas; Ndahafa Frans; Pentikainen Ndumbu; Andreas Shiningavamwe; Gerhard van Rooyen; Ferlin Schiceya; Lindile Hlahla; Pendapala Namundjebo; et al. (PLoS ONE, 2022)
Background As new SARS-CoV-2 variants of concern emerge, there is a need to scale up testing to minimize transmission of the Coronavirus disease 2019 (COVID-19). Many countries especially those in the developing world continue to struggle with scaling up reverse transcriptase polymerase reaction (RT-PCR) to detect SARS-CoV-2 due to scarcity of resources. Alternatives such as antigen rapid diagnostics tests (Ag-RDTs) may provide a solution to enable countries scale up testing. Methods In this study, we evaluated the Panbio™ and STANDARD Q Ag-RDTs in the laboratory using 80 COVID-19 RT-PCR confirmed and 80 negative nasopharyngeal swabs. The STANDARD Q was further evaluated in the field on 112 symptomatic and 61 asymptomatic participants. Results For the laboratory evaluation, both tests had a sensitivity above 80% (Panbio™ = 86% vs STANDARD Q = 88%). The specificity of the Panbio™ was 100%, while that of the STANDARD Q was 99%. When evaluated in the field, the STANDARD Q maintained a high specificity of 99%, however the sensitivity was reduced to 56%. Conclusion Using Ag-RDTs in low resource settings will be helpful in scaling-up SARS-CoV-2 testing, however, negative results should be confirmed by RT-PCR where possible to rule out COVID-19 infection.